Evaluación de los procesos actuales de confección para el mejoramiento de la productividad en la empresa LANAFIT S.A. Elaboración de un manual de procedimientos. - Andrango Guayasamín, Delia Isabel (2015)
This study has as its purpose the evaluation of the current processes of clothing in the company Lanafit S.A., to improve productivity through a standardization of procedures. In the development of the research is analyzed the current system of production, by lifting process information, and then raising a manual of procedures to assist in making garments. The proposed study is presented as a non-experimental research and takes a form of field, applying tools such as observation and documentary review to assess the process of clothing in the company. The obtained results allowed identifying operational problems during the process as well as low productivity due to the lack of instructions for the garment making. Next it arises a proposal through the elaboration of a manual of procedures. This research allowed us to analyze some case studies and options to improve the productivity and profitability in the production of clothing. It is concluded that the organization has specific characteristics in the process, where operators play a key role for a proper efficiency through the use of instructional work. The introduction of new technologies and proven updates, allow you to reduce operational costs and optimize the capacity of the plant in ways that enhance their statistics.